Analysis Of Promotion Strategies For 'Aa Deden's Pancong Business - Ridwan, Zulkifli M; Yulianti, Siska; Al Azma, Asy Syaffa Nur; Juliyanti, Karmila; Vela, Wilandiana (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
Micro, Small and Medium Enterprises are businesses run by individuals or small groups that meet certain requirements. Warung Pancong AA Deden is a culinary business that sells pancong products with various flavors and toppings. This study aims to determine effective promotional strategies in the Warung Pancong AA Deden business and to determine the effectiveness of word-of-mouth promotion. This study uses a qualitative research design by conducting observations, interviews and documentation. Data analysis in this study is supported by relevant theories, is descriptive and focuses on the process and meaning (from the subject's perspective), qualitative data research obtained through direct interviews with the owner of the Warung Pancong AA Deden business to obtain detailed and accurate information without using questionnaires. UMKM Kue Pancong AA Deden still relies heavily on word of mouth promotion because most of its consumers come from the Ciuyah, Cisarua area, Information through satisfied customers after enjoying pancong. To expand market reach, it is necessary to expand the use of technology and improve logistics. Promotional steps do not only stop at social media posts, but must also be accompanied by the development of a better packaging system. The marketing strategy at Warung Pancong AA Deden can be concluded as having potential for growth due to its product advantages, such as its unique taste, soft texture, and diverse flavors. Its affordable price tag attracts consumers. However, it still faces major challenges, particularly in digital marketing. Current promotions rely heavily on word of mouth (WOM).